KETERLIBATAN ORANG TUA DALAM MENDUKUNG PENDIDIKAN ANAK PADA USIA DINI DI KORONG TIRAM, KECAMATAN ULAKAN TAPAKIS, KABUPATEN PADANG PARIAMAN - Silvia Herlina (Ensiklopedia of Journal, 2022)
This study aims to describe the form of parental involvement in supporting children's education at an early age, as well as to find out the obstacles faced by parents in supporting children's education at an early age. This research uses a qualitative approach with descriptive analysis research type. The focus of the research is the form of parental involvement. The activity stages are the planning stage, the implementation stage, and the report results stage, the data sources used are primary and secondary data. The instrument used in this study was an interview guide sheet, data collection procedures, namely observation, interviews and documentation. Checking the validity of the data, namely technical triangulation and source triangulation, while the data analysis used is to explain, describe, and describe according to the problem. The results showed that the involvement of parents in supporting children's education at an early age in Korong Tiram, Ulakan Tapakis sub-district, Padang Pariaman district can be seen in terms of (1) parental participation in activities held at school. Activities that also involve parents in early childhood education programs are annual activities such as excursions or farewells. (2) When viewed from the involvement of parents in terms of providing education and assisting the educational development of their children, not all parents play an active role in providing education and assisting the educational development of their children in the home or family. there are some parents who are busy with their own business so that they neglect their children and seem not to care about their children's affairs. This causes many children to experience psychological problems such as children who act naughty, seek people's attention, are moody, disturb friends and so on.